2013
DOI: 10.1371/journal.pone.0079157
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Dioxide Is a Size-Selective Antimicrobial Agent

Abstract: Background / AimsClO2, the so-called “ideal biocide”, could also be applied as an antiseptic if it was understood why the solution killing microbes rapidly does not cause any harm to humans or to animals. Our aim was to find the source of that selectivity by studying its reaction-diffusion mechanism both theoretically and experimentally.MethodsClO2 permeation measurements through protein membranes were performed and the time delay of ClO2 transport due to reaction and diffusion was determined. To calculate ClO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 33 publications
1
83
2
8
Order By: Relevance
“…ELISA, enzyme-linked immunosorbent assay H 2 O 2 is a toxic disinfectant that is known as a source of oxidative stress in the cell to damage cells oxidatively. 62 Disinfectants are toxic nature at higher concentration 63,64 and a primary concern involves its environmental persistence, and hence, its long-term toxic effects on human. 58,59 In our current study, it is observed that overproduction of ROS leads to a similar effect.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA, enzyme-linked immunosorbent assay H 2 O 2 is a toxic disinfectant that is known as a source of oxidative stress in the cell to damage cells oxidatively. 62 Disinfectants are toxic nature at higher concentration 63,64 and a primary concern involves its environmental persistence, and hence, its long-term toxic effects on human. 58,59 In our current study, it is observed that overproduction of ROS leads to a similar effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, HOCl and other liquid disinfectants have less permeability in the soil. 44 As the pH range of common soil is about 5-8, the effect of pH on the disinfection is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Az eredményül kapott nanoszálak szabály-talan szerkezetű szövetet alkotnak (2. ábra, bal oldal), ez kompakt, körülbelül 1 mm vastagságú (2. ábra, jobb oldal). A hálót beültetés előtt ClO 2 -oldattal sterilizáltuk [12].…”
Section: Az Electrospinning Folyamataunclassified
“…A hálókat 2 M sósavoldattal előkezeltük és ClO 2 -vel sterilizáltuk. A kísérletek azt is igazolták, hogy a ClO 2 nincs negatív hatással a sejtek életképességére és osztódására, antibiotikus hatása pedig jól ismert [12]. A kontrollcsoportban A-549 sejteket helyeztünk el médiumban, hálók nélkül.…”
Section: In Vitro Vizsgálatokunclassified